Scenarios the art of strategic conversation - Van der Heijden, Kees. (Chichester West Sussex, 2005)
Scenario planning allows companies to move away from linear thinking and better understand external change. Eight years (and 30,000 copies) after publication Scenarios is still acknowledged as the definitive work in the field. Now, Kees van der Heijden brings his bestseller up to date, following up on his original case studies and adding significant new material. The Second Edition changes focus slightly by providing more in-depth analysis and application of the concept of the 'strategic conversation'. While maintaining the underlying rigour of the first edition, van der Heijden revisits the text to make it far more practical and accessible, and in doing so gives you the tools you need to set out and negotiate a successful future course for your organization in the face of significant uncertainty.
Includes bibliographical references (p. [347]-350) and index.
Keywords: Communication in management